UM OLHAR DE CIGANA: REPRESENTAÇÕES DE CAPITU EM GRAPHIC NOVEL - Costa, Marcia (2018)
With the emergence of the cultural studies, many changes occurred in Art and Literature. What was not previously seen as cultural production started to gain space, providing visibility to marginalised creations. Consequently, several works were adapted to diverse ways of propagation, such as the adaptation of the book Dom Casmurro to comic books. This study aims to analyse the relations of intertextuality between three comic books and the literary work, Dom Casmurro, as well as to perceive which passages of the book written in 1899 by Machado de Assis were adopted in this current rereading. It also seeks to understand how the authors have attempted to maintain the original features of the book and finally, if they have managed in fact to do so. Will be used as a theoretical support to approach the Cultural Studies the authors Ecosteguy (2010), Cevasco (2010) and Hall (2003). To address the literary classics, Pesavento (2003) and Calvino (1993). To cover the reception theory, Jauss (1994) and Iser (1999). To refer to adaptions and comic books, Hutcheon (2013), Eisner (1989) and Chenin, Vergueiro & Ramos (2014), among other theorists. In addition, we focused in our reflexions towards the relations of intertextuality between sequential art, which tells stories, and the literary work from Machado de Assis.